Microrna expression and assessment of potential role of miR-181a in head and neck cancer - Ab Mutalib, Nurul Syakima (2012)
MicroRNAs (miRNAs) represent a class of small non-coding RNAs that regulate gene expression by either inducing mRNA degradation or repressing mRNA translation. The involvements of miRNAs in various human cancer-related processes have been studied in recent years. The first objective of this study was to determine differentially expressed miRNAs in head and neck cancer. Global miRNA profiling was performed on 12 tissue samples from various head and neck cancers by using the microarray approach followed by real time RT-PCR validation. The microarray analyses identified 10 miRNAs that were able to distinguish malignant from normal tissues whereby seven miRNAs (hsa-miR-181a-2*, hsa-miR-29b-1*, hsa-miR-181a,hsa-miR-181b, hsa-miR-744, hsa-miR-1271 and hsa-miR-221*) showed upregulation while three miRNAs (hsa-miR-141, hsa-miR-95 and hsa-miR-101) showed down-regulation. Therefore, these miRNAs may aid in simple profiling strategies to identify individuals at higher risk of developing head and neck cancers, as well as elucidate the molecular mechanisms involved in head and neck cancers pathogenesis. The second objective of this study was to identify the putative targets of miRNAs differentially expressed in head and neck cancers and the pathways involved, which was achieved through in silico analysis aided by online databases, whereby several cancer-associated genes and pathways were found to be targeted by miR-181a. The role of miR-181a in head and neck carcinogenesis was subsequently determined through functional analyses as the third objective of this study. It was found out that miR-181a regulates the proliferation, migration, invasion and colony-forming ability of head and neck cancer cell. Fourth objective was achieved by using pathway analysis to profile changes in the activities of 10 signaling pathways related to cancer caused by miR-181a downregulation. Six of these pathways, namely the p53/DNA damage, TGFβ, MAPK/ERK, MAPK/JNK, Wnt and NFκB pathways, were found to be significantly influenced, suggesting miR-181a may act as an oncomiR, and therefore its inhibition may be a potential therapeutic target for head and neck cancer patients. The fifth and final objective of this study involved visualizing miR-181a expression and localization in head and neck tissues, for which in situ hybridization was utilized. miR-181a is preferentially expressed in the cytoplasm of cancer cells, and its expression is significantly increased in malignant compared to benign tumors of the head and neck. Collectively, these findings provide basis for study into the role of miR-181a as a biomarker and/or therapeutic target in head and neck tumors.